Measuring the impact of dyslexia - Hayes, Carol (Routledge, 2021)
"Measuring the Impact of Dyslexia shows the considerable benefits of recognising and celebrating the skills of those with information processing differences, explains their unique brain organisation and shows how they can excel as contributing members of society with proper support and guidance. It offers a balanced and research-based perspective to living with this condition, highlighting the huge number of children leaving school with low literacy levels, as a result of undiagnosed information processing differences. Full of critically-reflective questions, case studies and interviews with those affected by dyslexia, this text encourages educators of children and young people with dyslexia to challenge their own perceptions by understanding the links between low literacy and anti-social behaviour, poor health, unemployment and limited educational attainment, and includes helpful pointers for improving practice and outcomes. This accessible and readable text is aimed at students, practitioners, researchers and experienced professionals in a range of disciplines to enhance CPD. It is particularly relevant for students working on both taught and research based master's degrees, especially programmes related to specific learning difficulties"--
Chapter 1. Introduction to dyslexia -- Chapter 2. Help! I'm drowning! -- Chapter 3. The cost to family and friends -- Chapter 4. Health and mental health -- Chapter 5. The cost to education and social service -- Chapter 6. The criminal justice system -- Chapter 7. Employment: cost to employers / employees -- Chapter 8. Balancing the books: advantages to society -- Chapter 9. Research and academia -- Chapter 10. The great dyslexia industry -- Chapter 11. Politics, politics and policy.
Keywords: Dyslexia; Dyslexia; Dyslexics